„Testamentowa” „teoria” sprawiedliwości - Bartula, Piotr (Annales. Etyka w Życiu Gospodarczym, 2009)
Important problems of justice are raised by a project according to which the sovereign gives to victims the right to pardon a wrongdoer orally or in a testament. The author supports such an individualization of the right to pardon, which would turn the state into a contractor who is hired by citizens exclusively to guarantee them security and self-possession.